Medical errors in Orthopedics: Causes and preventions. - Joshi, Amit (Nepal Orthopaedic Association Journal, 2023)
While Nepal faces unique challenges in the healthcare system, including limited resources and geographical barriers, there have been notable developments in orthopedics. The number of orthopedic surgeons has significantly increased. Hence, orthopedic services are now available in all the corners of the country. Orthopedic interventions are now provided even in remote areas with the establishment of government and private hospitals. With the increase in health care delivery, even in resource-limited regions of the country. Medical errors have also increased.